Early reoperation in pediatric surgery at the Teaching Hospital Gabriel Touré. - Yacaria, Coulibaly; Issa, Amadou; Aliou, Doumbia; Oumar, Coulibaly; BenoÃ®t, Kamate; Kassoum, DjirÃ© Mamadou; Bernard, Coulibaly Mamadou; Souleymane, Diaby (Iranian Journal of Pediatric Surgery, 2019)
Introduction: To identify complications requiring early reoperation and to determine associated risk factors in the pediatric surgery of the teaching hospital Gabriel Toure. Materials and Methods: A retrospective study of children 0-15 years old during 4 years (January 2014 to December 2017) presenting with a postoperative complication requiring a reoperation and taken care of during the period of study. Observation of bowels or the liquid stools through the opened wound, the presence of air-fluid levels on an abdominal plain X-ray and the absence of resumption of intestinal transit allowed us to make a decision to re-operate. Results: We have re-intervened on 103 patients because of early postoperative complication out of 4730 cases of pediatric surgery carried out in this hospital during these 4 years. This represented 1.54 % of our total surgical activities. The average age of our patients was a 5.2±2.3 year ranging from 2 months to 15 years. The sex ratio was 0.94. Eighty four (81.55 %) of our patients were admitted and operated on emergently. Peritonitis due to digestive system perforation represented 45.28 % of the indications for reoperation followed by the acute intestinal intussusceptions (10.7 %) and traumatic eviscerations (9.7 %). The average duration before the first intervention was 80±13.6mn. The postoperative evisceration was the 1st cause of reoperation followed by the post-operative peritonitis and then post-operative intestinal obstruction. The average time to reoperation was 6.9 ± 4.2 days. Conclusion: In our hospital risk of reoperation has an association with: indication of first surgery, operating technique, experience of the surgeon, malnutrition and anemia (p<0.05). On the other hand sex, age and the duration of surgery have no effect on early reoperation (p > 0.05).